Double Disillusion: The 2016 Australian Federal Election 2018
DOI: 10.22459/dd.04.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

The Industrial Relations Policy and Penalty

Abstract: This chapter examines the role of industrial relations (IR) in the 2016 election, one that featured campaigns by and about (that is, against) trade unions. I commence with a brief history of industrial relations in Australian elections over several decades, including the 2007 'Your Rights at Work' (YRAW) campaign. I then discuss the parties' positioning on IR in the lead-up to the election over 2013-15, including two major inquiry reports. This is followed by the role played by key IR issues in the double diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Financial capital can also be utilized to invest in other profitable opportunities, which in total boosts the firms' productivity. Larger firms may be more competent in productive efficiency (Peetz, 2012). Florin et al (2003) suggested that with the help of social ties and networks, firms can spot more lucrative investment opportunities, in which they invest financial capital that generates productive efficiency.…”
Section: Ce and Productive Efficiencymentioning
confidence: 99%
“…Financial capital can also be utilized to invest in other profitable opportunities, which in total boosts the firms' productivity. Larger firms may be more competent in productive efficiency (Peetz, 2012). Florin et al (2003) suggested that with the help of social ties and networks, firms can spot more lucrative investment opportunities, in which they invest financial capital that generates productive efficiency.…”
Section: Ce and Productive Efficiencymentioning
confidence: 99%